Genetic diversity and antibody responses against Plasmodium falciparum vaccine candidate genes from Chhattisgarh, Central India: Implication for vaccine development. - Priyanka Patel; Praveen K Bharti; Devendra Bansal; Rajive K Raman; Pradyumna K Mohapatra; Rakesh Sehgal; Jagadish Mahanta; Ali A Sultan; Neeru Singh (PLoS ONE)
The genetic diversity in Plasmodium falciparum antigens is a major hurdle in developing an effective malaria vaccine. Protective efficacy of the vaccine is dependent on the polymorphic alleles of the vaccine candidate antigens. Therefore, we investigated the genetic diversity of the potential vaccine candidate antigens i.e. msp-1, msp-2, glurp, csp and pfs25 from field isolates of P.falciparum and determined the natural immune response against the synthetic peptide of these antigens. Genotyping was performed using Sanger method and size of alleles, multiplicity of infection, heterogeneity and recombination rate were analyzed. Asexual stage antigens were highly polymorphic with 55 and 50 unique alleles in msp-1 and msp-2 genes, respectively. The MOI for msp-1 and msp-2 were 1.67 and 1.28 respectively. A total 59 genotype was found in glurp gene with 8 types of amino acid repeats in the conserved part of RII repeat region. The number of NANP repeats from 40 to 44 was found among 55% samples in csp gene while pfs25 was found almost conserved with only two amino acid substitution site. The level of genetic diversity in the present study population was very similar to that from Asian countries. A higher IgG response was found in the B-cell epitopes of msp-1 and csp antigens and higher level of antibodies against csp B-cell epitope and glurp antigen were recorded with increasing age groups. Significantly, higher positive responses were observed in the csp antigen among the samples with ≥42 NANP repeats. The present finding showed extensive diversity in the asexual stage antigens.